2015
DOI: 10.1002/mus.24606
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic evaluation of rhabdomyolysis

Abstract: Rhabdomyolysis is characterized by severe acute muscle injury resulting in muscle pain, weakness, and/or swelling with release of myofiber contents into the bloodstream. Symptoms develop over hours to days following an inciting factor and may be associated with dark pigmentation of the urine. Serum creatine kinase and urine myoglobin levels are markedly elevated. The clinical examination, history, laboratory studies, muscle biopsy, and genetic testing are useful tools for diagnosis of rhabdomyolysis, and they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
155
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(185 citation statements)
references
References 215 publications
3
155
0
12
Order By: Relevance
“…By contrast, their causing of rhabdomyolysis is extremely rare, probably only at a rate of 0.4 per 10,000 person per year [16]. Despite such a low incidence rate, certain drugs such as amiodarone that this patient has been taking to control ventricular rate could increase the risk of rhabdomyolysis when combined with statins [16]. In fact, a review of the United States Food and Drug Administration post-marketing database of rhabdomyolysis (CK 10,000) showed that, of 866 cases reported between 1987 and 2001, 44% were related to combination therapy, as compared with statins alone [22].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…By contrast, their causing of rhabdomyolysis is extremely rare, probably only at a rate of 0.4 per 10,000 person per year [16]. Despite such a low incidence rate, certain drugs such as amiodarone that this patient has been taking to control ventricular rate could increase the risk of rhabdomyolysis when combined with statins [16]. In fact, a review of the United States Food and Drug Administration post-marketing database of rhabdomyolysis (CK 10,000) showed that, of 866 cases reported between 1987 and 2001, 44% were related to combination therapy, as compared with statins alone [22].…”
Section: Discussionmentioning
confidence: 98%
“…Mild and subclinical cases of rhabdomyolysis, called in clinical practice myopathies, are typically characterized by elevated serum CK and myalgias [15]. The diagnosis of rhabdomyolysis is primarily based on myoglobinuria or a marked elevation in serum CK [16,17]. Rhabdomyolysis accounts for 13%-50% of AKI cases [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ez klasszikus formájában csak a betegek mintegy 10%-ánál jelentkezik, és a felnőtt betegek fele nem említ izomfájdalmat. A fenti izompanaszokat olykor (8-15%) még az izmok megduzzadása is kíséri [5,6].…”
Section: Rhabdomyolysisunclassified